Nativization and Standardization of Nigerian Pidgin (Naija): A Study of its Expanding Domains and Attitudes - Ndifon, Mamina M; Ghevolor, Asa; Ekoro, Daniel; Okpene, Dominic; Edung, Augustine (Indonesian Journal of Educational Studies, 2025)
This research investigates the ongoing processes of nativization and potential standardization of Nigerian Pidgin (Naija) by examining its expanding functional domains and mapping contemporary societal attitudes. Once primarily a lingua franca for trade and informal interaction, Naija is now nativized as a first language for a growing urban population and is permeating high-prestige domains such as popular music (Afrobeats), cinema (Nollywood), broadcast media, social media, and political discourse. This study employs a mixed-methods approach, combining sociolinguistic questionnaires to gauge attitudes from a diverse demographic with critical discourse analysis of Naija usage in select media and online platforms. The research aims to determine whether these expanding domains are fostering a de facto standard variety and to what extent this influences the language’s prestige. Findings will illuminate the complex interplay between language use, identity, and power in modern Nigeria, contributing to debates on its official status. Ultimately, this study provides crucial insights into the dynamic evolution of Naija from a contact language to a potent, full-fledged national symbol capable of expressing the complete range of human experience in the Nigerian context.